Disproportional changes of glucose, lactic acid and haemoglobin level as parameters for physical performance test - Sri Rahajoe Asj'ari Sri Rahajoe Asj'ari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Levels of blood Hb, glucose and lactic acid were estimated two times to 49 athletes of badminton and tennis (13-27 years old). The estimations were done before and after physical performance test. The loads of physical performance test for the subjects were different to each other, depending on their capacities. The changes of Hb concentration were used to correct the changes of glucose and lactic acid concentrations due to the changes of blood volume. The Hb concentrations of 35 subjects increased and the rest of 14 decreased; they were called group A (n=35) and group B (n=14) respectively. When blood glucose concentrations were observed from group A, 24 of them decreased (group At) while the remaining 11 increased. After it had been adjusted to the changes of blood volume, the blood glucose concentration of 4 among the 11 persons (group A2) became lower, while the other 7 subjects remained high (group A3). Blood glucose concentrations of group B increased even after adjusted to the changes of blood volume. The lactic acid concentrations of all subjects also increased after adjusted to the changes of blood volume.Key words: athletes blood haemoglobin glucose lactic acid physical performance